Análisis de enriquecimiento ilícito y auditoría forense en los exámenes de declaraciones patrimoniales juradas - López Veloz, Marianela Edith (2022)
The objective of this article is to show how the forensic audit helps in the execution of the reviews of patrimonial declarations to determine the presumptions of illicit enrichment, since these techniques are not regulated in Ecuador, but they are executed in these types of exams. This research studies the process of the special examination of sworn statements to a public servant based on the regulations issued by Contraloría General del Estado, which is the institution that analyzes the content of the patrimonial declarations presented at the beginning and end of the management of the servers. public in accordance with the periodicity established by current regulations. The examination was carried out according to a planned, unforeseen schedule or due to allegations of illicit enrichment presumptions, which after a forensic audit concluded with a report the presumption of unjustified illicit enrichment. According to the legal procedures, this report was sent to the (FGE) for the corresponding investigations according to the free versions by the team leader and supervisor in the execution of the audit examination, in which the audit team used the forensic audit techniques to determine the illicit enrichment that was later called to trial. Of the investigations carried out by the FGE, the unjustified enrichment of the public servant was determined, to which the Corte Nacional sentenced him with the deprivation of liberty, the same person who is serving a prison term of two years. This case was the first in Ecuador for illicit enrichment and represents a fundamental precedent of corruption.